A conductive heat transfer model for particle flows over immersed surfaces. (October 2015) - Morris, A.B.; Pannala, S.; Ma, Z.; Hrenya, C.M.
Highlights: Discrete particle simulations model conductive heat transfer to flowing particles. Wall heat transfer is very sensitive to solids concentration near the wall. A new continuum heat transfer model captures solids concentration effects. The new continuum model closely agrees with discrete particle simulation data. Abstract: A fundamental continuum model for conductive heat transfer between an immersed boundary and flowing particles is developed. The model is derived for systems where conduction through the interstitial gas between nearby surfaces is the dominant heat transfer mechanism. Conductive heat transfer depends on the thermal properties of the solids and gas phases, particle size and morphology, and packing structure. The new model incorporates both particle size and arrangement effects using first principles, and is applicable to flows spanning dilute to dense regimes. Specifically, a novel particle–wall distribution function is employed to capture the effects of particle arrangement over a range of solids concentrations. Discrete element method (DEM) simulations are used to close the model in terms of continuum variables and to generate constitutive relations for the Nusselt number and local heat transfer coefficient. The resulting expression is implemented into a continuum gas–solid model and tested against DEM data for particle flow down a ramp, flow around a hexagon, and crossflow around a cylinder. The model accurately predicts the local heat transfer coefficient over a range of flow parameters, and is valid for the full range of solids concentrations.